AN ERROR ANALYSIS OF ENGLISH FOREIGN LANGUAGE LEARNING IN THE TERMINAL MOVIE - Suswanto Ismadi Megah S. (CAHAYA PENDIDIKAN, 2016)
This study identified how the foreigner survived in communication when he ‘trapped’ almost a year at the John F. Kennedy International Airport. human being needs to interact with others as they fulfill their needs by using communication tool such as language in a society. Hence, this study idenfied how he learnt at the airport to communicate with other people. it is important thing of human life, people need communication to share idea, opinion, or feelings to others. In addition,  good interaction when they can communicate their tough well. But the problem is conducting a good relationship with the others is not an easier matter. This study took data from transcription of the dialoque of the main character. The data analyzed descriptively. To have speaking ability, student must be train to use English in communication orally.Eventually, the result of the study shows that the main character could communicate English well.  Keywords: Analysis, Error, and Foreign Language Learning.